Pengalaman dan Kepuasan Berpengaruh Positif terhadap Loyalitas Pelanggan Gofood di Jakarta - Audina, Clara; Rakhman, Abdullah (Jurnal Manajemen, 2023)
The developments in the internet and related technology have switched business digitally. One of the digital businesses known widely is an online food delivery service, GoFood. With the growth of the online food delivery service business, the business players in the industry struggle for the most crucial factor for success: customer loyalty. The need for customer loyalty forces GoFood to ensure customers experience positive service and are satisfied. However, empirical confirmation of this notion is still not fully available. This study is purposed to find such a necessity in the GoFood context. Therefore, the authors collected the data from 190 GoFood customers chosen judgmentally. Data analysis with multiple linear regression analysis reveals that customer experience and satisfaction positively and significantly affect customer loyalty with a determinant coefficient of 42.2%. Further research can replicate this study constructively by adding a structural path from customer experience to customer satisfaction.